Prinsip-Prinsip Hukum Islam dalam Peraturan Daerah: Melacak Motivasi dan Efektifitas Perda Bernuansa Syariah di Pamekasan - Maimun Maimun; Ainul Haq (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
The presence of several Regional Regulations (Perda) with shari'a nuance in Pamekasan is expected to make his community more behave Islam . But the lofty desire has not been fully realized according to the ideals of its formation. This research tries to find out what exactly is behind the (motivation) of the issuing of Regional Regulations with shari'a nuance in Pamekasan, and how is the effectiveness of applying Regional Regulations  with shari'a nuance in Pamekasan . Through a qualitative - phenomenological approach with the type of field research  and descriptive  analysis  of Miles model and Huberman, it produced some findings: First, the motivation behind the establishment of Regional Regulations  with shari'a nuance was not only because of heir philosophical-sociological and juridical elements but also  the existence of motives of  identity politics integrated with  law politics . Second , the implementation of  Regional Regulations  with shari'a nuance has not been maximum  and effective in forming the behavior of  Pamekasanese society more  Islamic. Many factors that made the problem emerge, neither because of many regional regulations that their enforcement were ignored  in the field  nor because of  the  presence of the regional regulations that were contradictory with other regional regulations.